Mirabegron does not adversely impact cognitive function in older adults with overactive bladder compared to placebo - Sanjna Ghanshani; Abbie R Bauer (Clinical Research In Practice: The Journal of Team Hippocrates, 2024)
A clinical decision report using: Griebling TL, Campbell NL, Mangel J, et al. Effect of mirabegron on cognitive function in elderly patients with overactive bladder: MoCA results from a phase 4, randomized, placebo-controlled study (PILLAR). BMC Geriatr. 2020;20(1):109. https://doi.org/10.1186/s12877-020-1474-7 for a patient with a history of lacunar infarctions who is experiencing urge incontinence.